Twenty-first-century demographic and social inequalities of heat-related deaths in Brazilian urban areas - Monteiro dos Santos, Djacinto; Libonati, Renata; Garcia, Beatriz N.; Geirinhas, João L.; Salvi, Barbara Bresani; Lima e Silva, Eliane; Rodrigues, Julia A.; Peres, Leonardo F.; Russo, Ana; Gracie, Renata; Gurgel, Helen; Trigo, Ricardo M. (PloS one, 2024)
Population exposure to heat waves (HWs) is increasing worldwide due to climate change, significantly affecting society, including public health. Despite its significant vulnerabilities and limited adaptation resources to rising temperatures, South America, particularly Brazil, lacks research on the health impacts of temperature extremes, especially on the role played by socioeconomic factors in the risk of heat-related illness. Here, we present a comprehensive analysis of the effects of HWs on mortality rates in the 14 most populous urban areas, comprising approximately 35% of the country’s population. Excess mortality during HWs was estimated through the observed-to-expected ratio (O/E) for total deaths during the events identified. Moreover, the interplay of intersectionality and vulnerability to heat considering demographics and socioeconomic heterogeneities, using gender, age, race, and educational level as proxies, as well as the leading causes of heat-related excess death, were assessed. A significant increase in the frequency was observed from the 1970s (0–3 HWs year -1 ) to the 2010s (3–11 HWs year -1 ), with higher tendencies in the northern, northeastern, and central-western regions. Over the 2000–2018 period, 48,075 (40,448–55,279) excessive deaths were attributed to the growing number of HWs (>20 times the number of landslides-related deaths for the same period). Nevertheless, our event-based surveillance analysis did not detect the HW-mortality nexus, reinforcing that extreme heat events are a neglected disaster in Brazil. Among the leading causes of death, diseases of the circulatory and respiratory systems and neoplasms were the most frequent. Critical regional differences were observed, which can be linked to the sharp North-South inequalities in terms of socioeconomic and health indicators, such as life expectancy. Higher heat-related excess mortality was observed for low-educational level people, blacks and browns, older adults, and females. Such findings highlight that the strengthening of primary health care combined with reducing socioeconomic, racial, and gender inequalities represents a crucial step to reducing heat-related deaths.